Systematic Identification and Analysis of Acinetobacter baumannii Type VI Secretion System Effector and Immunity Components - Lewis, Jessica M.; Deveson Lucas, Deanna; Harper, Marina; Boyce, John D. (Frontiers in Microbiology, 2019)
Many Gram-negative bacteria use a type VI secretion system (T6SS) for microbial warfare and/or host manipulation. Acinetobacter baumannii is an important nosocomial pathogen and many A. baumannii strains utilise a T6SS to deliver toxic effector proteins to surrounding bacterial cells. These toxic effectors are usually delivered together with VgrG proteins, which form part of the T6SS tip complex. All previously identified A. baumannii T6SS effectors are encoded within a three or four gene locus that also encodes a cognate VgrG and immunity protein, and sometimes a chaperone. In order to characterize the diversity and distribution of T6SS effectors and immunity proteins in this species, we first identified all vgrG genes in 97 A. baumannii strains via the presence of the highly conserved VgrG domain. Most strains encoded between two and four different VgrG proteins. We then analysed the regions downstream of the identified vgrG genes and identified more than 250 putative effectors. The presence of conserved domains in these effectors suggested a range of functions, including peptidoglycan hydrolases, lipases, nucleases, and nucleic acid deaminases. However, 10 of the effector groups had no functionally characterised domains. Phylogenetic analysis of these putative effectors revealed that they clustered into 32 distinct groups that appear to have been acquired from a diverse set of ancestors. Corresponding immunity proteins were identified for all but two of the effector groups. Effectors from eight of the 32 groups contained N-terminal rearrangement hotspot (RHS) domains. The C-terminal regions of these RHS proteins, which are predicted to confer the toxic effector function, were very diverse, but the N-terminal RHS domains clustered into just two groups. While the majority of A. baumannii strains contained an RHS type effector, no strains encoded two RHS effectors with similar N-terminal sequences, suggesting that the presence of similar N-terminal RHS domains leads to competitive exclusion. Together, these analyses define the extreme diversity of T6SS effectors within A. baumannii and, as many have unknown functions, future detailed characterization of these effectors may lead to the identification of proteins with novel antibacterial properties.